Expectation gap between auditors and users of financial statements - Chin, Wee Peng (2014)
The past decade has been witness to a dramatic increase in the number of lawsuits against auditors. This increased number was evident in the United States as early as 1974. Due to certain structural differences in jurisdiction, Singapore has remained relatively non-litigious but the overseas situation has been felt here in terms of an increase in premium for professional indemnity insurance. Some of the cases against auditors are due to genuine negligence on the part of the auditor, others are due to misconceptions by the public of the auditor’s role and responsibilities (expectation gap).